PEMANFAATAN GULMA BANDOTAN MENJADI PESTISIDA NABATI UNTUK PENGENDALIAN HAMA KUTU KUYA PADA TANAMAN TIMUN - Sultan Sultan; Patang Patang; Subari Yanto (Universitas Negeri Makassar, 2016)
This study aims to know the possibility of Ageratum conyzoides L. used asan organic pesticideand Ageratum conyzoides L. concentration appropriatein controlling pest Aulocaphora sp. Oncucumber plant. This research is experimental research using completely randomised design. There arefour treatment that concentration (3%), concentration treatment (6%), concentration treatment (9%), and control which 3 repetition. Variable research observed behavior and mortality of pest Aulocaphora sp. The results showed Ageratum conyzoides L.extract use has the ability in controlling pest Aulocaphora sp.at concentration 9%, which can hamper the ability eat and cause silent reaction on pest Aulocaphora sp. furthermore, Aulocaphora sp. that eat the cucumber leaf lowest at concentration 9%